Curcuma longa extract reduces serum inflammatory markers and postprandial hyperglycemia in healthy but borderline participants with overweight and glycemia in the normal/prediabetes range: a randomized, double-blind, and placebo-controlled trial - Uchio, Ryusei; Okuda-Hanafusa, Chinatsu; Sakaguchi, Haruka; Saji, Ryosuke; Muroyama, Koutarou; Murosaki, Shinji; Yamamoto, Yoshihiro; Hirose, Yoshitaka (Frontiers in Nutrition, 2024)
The spice turmeric, which has the Latin name Curcuma longa (C. longa), has a range of various physiological effects. This study evaluated the effects on inflammation and glucose metabolism of a mixture of a hot water and mixture with supercritical carbon dioxide C. longa extracts, CLE, and of the potential active components of C. longa, turmeronols A and B and bisacurone on inflammation and glucose metabolism. First, we investigated the effect of CLE and the C. longa potential active components of C. longa on lipopolysaccharide-induced inflammation in RAW264.7 macrophages. We found a significant decrease in the production of interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α, and nitric oxide with CLE, turmeronol A, and bisacurone, and. significant Significant inhibition of all each of these substances was also observed, except for TNF-α with turmeronol B. The second part of our work was a 12-week randomized, double-blind, placebo-controlled study in healthy adults healthy but borderline adults aged 40 to 69 years with overweight and normal/prediabetes glycemia. We compared blood inflammatory and glycometabolic markers in the CLE (n = 55) and placebo groups (n = 55) and). We found significantly lower serum high-sensitivity C-reactive protein and hemoglobin A1c levels in the CLE group; this. This group also showed significant improvements in postprandial hyperglycemia and insulin sensitivity indices. Taken together, our Our findings indicate that CLE may reduce low-grade inflammation and thus improve insulin sensitivity and postprandial hyperglycemia.